2019
DOI: 10.1155/2019/3236526
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Surfaces of a Health Care Environment by Multidrug-Resistant (MDR) Bacteria

Abstract: Nosocomial infections (NIs) are known worldwide and remain a major problem despite scientific and technical advances in the field of health. The severity of the infection depends on the characteristics of the microorganisms involved and the high frequency of resistant pathogens in the hospital environment. The aim of this study is to determine the distribution of pathogenic bacteria (and their resistance to antibiotics) that spread on hospital surfaces, more specifically, on those of various departments in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 23 publications
5
42
2
3
Order By: Relevance
“…[24][25][26] The occurrence of antimicrobial resistance (AMR) is also increasing and resulting in higher morbidity and mortality associated with HCAIs. 23,27 In the present study, out of 164 environmental samples from swabs, 141 (86%) were positive for bacterial contamination which has similarly been reported from studies like Zimbabwe (86.2%) 14 and Morocco (96.3%). 28 In contrast to our result, studies conducted from Gaza Strip (24.7%), 29 Sudan (29.7%), 30 Uganda (44.2%), 31 Nigeria (39.4%), 32 and Bahir Dar, Northwest Ethiopia (39.6%) 16 reported far lower surface contamination rates.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[24][25][26] The occurrence of antimicrobial resistance (AMR) is also increasing and resulting in higher morbidity and mortality associated with HCAIs. 23,27 In the present study, out of 164 environmental samples from swabs, 141 (86%) were positive for bacterial contamination which has similarly been reported from studies like Zimbabwe (86.2%) 14 and Morocco (96.3%). 28 In contrast to our result, studies conducted from Gaza Strip (24.7%), 29 Sudan (29.7%), 30 Uganda (44.2%), 31 Nigeria (39.4%), 32 and Bahir Dar, Northwest Ethiopia (39.6%) 16 reported far lower surface contamination rates.…”
Section: Discussionsupporting
confidence: 85%
“… 24–26 The occurrence of antimicrobial resistance (AMR) is also increasing and resulting in higher morbidity and mortality associated with HCAIs. 23 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…It remains the best process for preventing the transmission of microorganisms and, consequently, minimizing the risk of infection, especially with the significant emergence of antibiotic resistance. The risk is higher with the increasing incidence of antimicrobial resistance [ 19 ]. The results obtained in our study showed a variation in efficacy, which may be attributed to many factors; the action of the active molecule of each disinfectant, the genus, and the structure of the bacteria isolated developed the resistance or not to the antimicrobial agent and the adopted disinfection protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The improved biocompatibility and lower toxicity of structurally engineered repellent materials would allow them to be used in a larger range of applications including the highly regulated food 146 and medical industries. 147 …”
Section: Emerging Technologies and Future Perspectivementioning
confidence: 99%